(untitled) (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2025)
Companies need human resources as important actors in the operational activities they carry out to achieve their goals. Increasing the role of human resources can be strengthened by paying attention to the motivational aspects and working environment conditions of employees when carrying out the tasks that have been assigned to them. This study aims to determine the impact of motivation and work environment on employee job satisfaction at PT Karya Zirang Utama Depok Branch. The saturated sampling method was used to obtain respondents and the data collection method was distributed to all employees totaling 48 people. The data analysis included a multiple regression test preceded by a validity and reliability test with the use of the SPSS 25 application for data processing. The findings of the study show that simultaneously motivation and work environment have a significant and positive influence on employee job satisfaction. Motivation partially has a significant influence on job satisfaction. However, the work environment does not show a significant influence on employee job satisfaction at PT Karya Zirang Utama Depok Branch.